Immunotherapy using lipopolysaccharide-stimulated bone marrow-derived dendritic cells to treat experimental autoimmune encephalomyelitis. (7th November 2014) - Zhou, F; Ciric, B; Zhang, G-X; Rostami, A
Summary: Lipopolysaccharide (LPS) produced by Gram-negative bacteria induces tolerance and suppresses inflammatory responses in vivo; however, the mechanisms are poorly understood. In this study we show that LPS induces apoptosis of bone marrow-derived dendritic cells (DCs) and modulates phenotypes of DCs. LPS treatment up-regulates expression of tolerance-associated molecules such as CD205 and galectin-1, but down-regulates expression of Gr-1 and B220 on CD11c + DCs. Moreover, LPS treatment regulates the numbers of CD11c + CD8 +, CD11c + CD11b low and CD11c + CD11b hi DCs, which perform different immune functions in vivo . Our data also demonstrated that intravenous transfer of LPS-treated DCs blocks experimental autoimmune encephalomyelitis (EAE) development and down-regulates expression of retinoic acid-related orphan receptor gamma t (ROR-γt), interleukin (IL)-17A, IL-17F, IL-21, IL-22 and interferon (IFN)-γ in myelin oligodendrocyte glycoprotein (MOG)-primed CD4 + T cells in the peripheral environment. These results suggest that LPS-induced apoptotic DCs may lead to generation of tolerogenic DCs and suppress the activity of MOG-stimulated effector CD4 + T cells, thus inhibiting the development of EAE  in vivo . Our results imply a potential mechanism of LPS-induced tolerance mediated by DCs and the possible use of LPS-induced apoptotic DCs to treat autoimmune diseases such as multiple sclerosis.